2013
DOI: 10.1049/iet-sen.2013.0013
|View full text |Cite
|
Sign up to set email alerts
|

Critical success factors for offshore software outsourcing contract management from vendors’ perspective: an exploratory study using a systematic literature review

Abstract: Offshore software development outsourcing is a recent and widely used business strategy for the development of high quality products at low cost. The objective of the research presented in this study is to find critical success factors (CSFs) for contract management to assist vendor organisations for successful outcomes of the offshore software outsourcing contract. A systematic literature review (SLR) process was performed for the identification of factors that can assist vendor organisations in successful ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 57 publications
(74 reference statements)
0
42
0
1
Order By: Relevance
“…If a barrier has got a frequency percentage ≥30%, we consider it to be a critical one. Other researchers have also used the similar approach . However, GSD practitioners may define their own criteria for deciding the significance of a barrier to be critical or not.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…If a barrier has got a frequency percentage ≥30%, we consider it to be a critical one. Other researchers have also used the similar approach . However, GSD practitioners may define their own criteria for deciding the significance of a barrier to be critical or not.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, we have found a total of 16 barriers in software integration which hurdle the integration process in GSD environment. Among these, 10 barriers have been ranked as critical barriers based on the 30% criteria used by many researchers in the literature . Table reveals that as compared to small and medium size projects the large size projects have been reported in the highest number of papers.…”
Section: Discussionmentioning
confidence: 99%
“…Tacit knowledge is a specific knowledge with unique content, which is difficult for structuring and diffusing, while explicit knowledge is easily distributed in formal and symbolic language [21]. Khan and Khan mentioned that contract flexibility, trustworthy relationship management, competitive bidding, consultation and negotiation, quality management, knowledge sharing, top management support, software process improvement certification, risk sharing attitude, time management, culture awareness, intellectual property right, data security and privacy, detailed specifications of product and project, conflict reconciliation mechanism are the important factors for successful outsourcing partnership, among which first five factors were identified as critical success factors [19].…”
Section: It Professionals Of 148 Banksmentioning
confidence: 99%
“…In many cases, IT outsourcing project starts with target settings where achievable success factors are also defined and selected (Chou and Chou, 2009). These factors give good indications for defining criteria to be used in final vendor selection.…”
Section: Introductionmentioning
confidence: 99%